Impact of Organizational Commitment for Tourism Supply Chain Management on Organizational Citizenship Behaviour by Mediation of Psychological Attachment and Work Alienation in Indonesian Tourism Industry - Hujaimatul Fauziah; Satria Bangsawan; Mahrinasari MS (International Journal of Supply Chain Management, 2020)
Organizational positive work behaviors of employees are very crucial for increasing their performance and organizational’ performance. Positive work behaviors of employees increased by increasing the positive psychological factors at workplaces. Aim of this study was to examine the impact of organizational commitment for tourism supply chain management (TSCM) on organizational citizenship behavior with mediation of work alienation and psychological attachment in employees working in tourism industry of Indonesia. Sample size calculated by simple random sampling method and data is collected through self-visited method and by questionnaires. Collected data tested by Smart PLS. generated results showed that TSCM has positive significant impact on organizational citizenship behavior and psychological attachment but has negative impact on work alienation. Psychological attachment has positive impact on organizational citizenship behaviors and also mediates the relation between TSCM and organizational citizenship behaviors. Work alienation has negative impact on organizational citizenship behavior but mediates the relation between TSCM and organizational citizenship behavior. Authorities of tourism industry should focus on organizational citizenship behavior because these factors increase the profit and performance of employees by increasing the psychological positive factors.